La represión de lo imaginario en el campo literario Mexicano del siglo XX - Vélez García, Juan Ramón (Acta Hispanica, 2010)
This work seeks to study, within the Mexican literary field of the XXth century, the situationof some authors who have been segregated from it because of their refusal to yield their work tothe requirements of nationalistic themes. I’m going to take as examples of the aforementionedideas two illustrative cases: the authors who were members of the group Contemporáneos (suchas Xavier Villaurrutia, José Gorostiza, Jorge Cuesta, Gilberto Owen, Salvador Novo…)and the writer Francisco Tario (pseudonym adopted by Francisco Peláez).